Quantification and Correction of Iris Color - Fan, Shaohua; Dyer, Charles; Hubbard, Larry (University of Wisconsin-Madison Department of Computer Sciences, 2003)
A system has been developed that automatically extracts the iris region from photographs, computes the iris color in CIE u 'v ' diagram color space, and corrects the color based on a standard calibration target. This system has advantages over previous manual methods in that it (I) is much less time-consuming because it is fully automatic, (2) corrects for the variability inherent in a film-based photographic process, (3) allows for greater objectivity and reproducibility, and (4) uses a mathematical foundation that enables quantification and statistical analysis. Preliminary experimental results show that color correction significantly improves grading accuracy.